PENGARUH MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIAOR (OCB) KARYAWAN PT. PELINDO III (PERSERO) CABANG TANJUNG PERAK SURABAYA - Hesty Dwi Febriani (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2016)
This research aims to find out and analyze the influence of motivation work towards organizational citizenship behavior (OCB) employees at pt. pelindo iii (persero) cabang Tanjung Perak Surabaya. this research is quantitative research. the subject of this research is the employees of PT. PELINDO III (persero) cabang Tanjung Perak Surabaya. The collection of data using questionnaires and interviews, sampling technique was simple random sampling (simple random sample), while data analysis is done using a simple linear regression analysis. based on the results of the study found that motivational variables work a positive and significant effect against the organizational citizenship behavior (OCB) employees PT. PELINDO III (persero) cabang tanjung perak surabaya. the regression equation obtained was y = 1.883 + x 1.328. the magnitude of the influence the motivation of working against the organizational citizenship behavior (OCB) employees at PT. PELINDO III (persero) cabang tanjung perak surabaya i.e. of 73.3% 23.7% while the rest is affected by other variables that are not incorporated into the model y = a + bx.